2021
DOI: 10.5114/aoms.2019.85459
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the macrophage migration inhibitory factor and polymorphisms in systemic lupus erythematosus: a meta-analysis

Abstract: IntroductionSeveral published results have established variations in respect to plasma/serum macrophage migration inhibitory factor (MIF) levels and gene polymorphisms with systemic lupus erythematosus (SLE). This study gave a more concise estimation on the MIF levels for SLE patients and established the association between MIF polymorphisms and SLE.Material and methodsAll articles were searched from PubMed, Embase, Web of Science, Wan-Fang, Chinese Biological Medical Literature, and China National Knowledge I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…MIF increased tumour cell proliferation by releasing cytokines including TNF-α, IL-1b and IL-6 (Kolostova et al, 2022). In our study, tissue levels of MIF, TNF-α and IL-1 were up-regulated in infected E. awoara; these results were similar to previously reported results (Sam et al, 2021).These results may offer a novel therapeutic strategy for treating bacterial disease.…”
Section: Mif Tnf-α and Il-1tissue Levelssupporting
confidence: 91%
“…MIF increased tumour cell proliferation by releasing cytokines including TNF-α, IL-1b and IL-6 (Kolostova et al, 2022). In our study, tissue levels of MIF, TNF-α and IL-1 were up-regulated in infected E. awoara; these results were similar to previously reported results (Sam et al, 2021).These results may offer a novel therapeutic strategy for treating bacterial disease.…”
Section: Mif Tnf-α and Il-1tissue Levelssupporting
confidence: 91%
“…In fact, a wide range of variations has been observed in healthy control groups in different studies. In one meta-analysis study (37), the healthy controls serum levels ranged from 0.3 ± 0.012 up to 61 ± 58.7 ng/mL (38) based on the studies included in the meta-analysis. Also, in another meta-analysis (27), the mean serum levels of the control groups among different studies ranged from 0.121 ± 0.001 up to 46.829 ± 38.394 ng/mL (39).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences indicate that the onset of LN may be correlated with oestrogen levels. However, several studies have reported regional and ethnic differences in terms of age at peak onset in men with LN [7][8][9][10]. Type IV LN is the most common pathological type in both male and female patients.…”
Section: Wbc -White Blood Cell Hb -Haemoglobin Esr -Erythrocyte Sedim...mentioning
confidence: 99%